Performance of Sudanese activated bentonite in bleaching cottonseed oil - Taha, Kamal K; Suleiman, Tagelsir M; Musa, Musa A (Journal of the Bangladesh Chemical Society, 2012)
Bentonite clay collected from Jabal Umm Ali area NE of Khartoum (Sudan) was characterized by X-ray diffraction (XRD). It was then purified by treatment with distilled water and activated with sulfuric acid at 90 ºC for 3.5 hrs. XRD indicated modification of activated bentonite with enhanced surface area. Several cations were removed from octahedral sheet (Mg, Al, and Fe). Increasing the acid concentration enhanced the degree of destruction of bentonite structure. On bleaching semi-refined cottonseed oil with activated bentonite, 30% acid concentration was found to be optimal for color removal and that the local activated bentonite is more efficient in bleaching vegetable oil than the standard one. DOI: http://dx.doi.org/10.3329/jbcs.v24i2.9708 Journal of Bangladesh Chemical Society, Vol. 24(2), 191-201, 2011